Perancangan Tindakan Pengurangan Komplain Produk Berkutu pada Perusahaan Tepung Terigu - Felicia Layrensius; I Nyoman Sutapa (Jurnal Titra, 2020)
Customer satisfaction is one of the main focus of company for giving service. Benchmark to find out the level of customer satisfaction is by the number of complaints customer delivered. The most frequently delivered type of complaint caused by weevil contamined products. Company would like to reduce number of complaints especially in the biggest causes. The analytical method is using gap analysis between Good Manufacturing Practices theory and the fact which is implemented by the company. Good Manufacturing Practice is a criteria that must be done by the processed food company, then if there is any criteria has not been fulfilled, it will be used as a guidance to identify the problem and designing corrective actions to reduce the number of complaints caused by weevil contamined product. Gap analysis result showed that company has already produced the processed food well overall, but some scopes still need improvement to reduce the number of complaints, such as packer in production process and sanitation facilitation in warehouse.